Chiral selectivity of polyglycerol‐based amphiphiles incorporating different aromatic cores. Issue 11 (30th July 2015) - Setaro, A.; Popeney, C. S.; Witt, M. U.; Bluemmel, P.; Glaeske, M.; Haag, R.; Reich, S.
Abstract : Customized polyglycerol‐based surfactants incorporating different aromatic cores are used to isolate and suspend carbon nanotubes in water. Different cores yield suspension with distinct chiral species distribution. Increasing the number of the phenyl rings connecting head and tail, the dispersion of the semiconducting species becomes sharper toward the nanotubes with bigger family index.